The Effect of Corporate Governance toward Dividend Payout Ratio - Werner Ria Murhadi; Regina Vanessa Tjipta; Endang Ernawati (Program MM Universitas Surabaya, 2022)
Pupose: The existence of market uncertainty can increase agency problems that raise doubts about future cash flows, such as dividend payments. This study aims to analyze the effect of corporate governance such as the proportion of female commissioners, the proportion of female independent commissioners, the board size, board independence, board meeting, and audit committee size towards a dividend payout ratio. Method:The sample of this research is manufacturing sector companies listed on the Indonesia Stock Exchange (ISE) and the Thailand Stock Exchange (TSE). The company should have published financial reports that have been audited regularly during the study period, and the company has no negative retained earnings. This study uses a quantitative approach with two least square regression analysis models. Result: The observations on the ISE shows that the proportion of female independent commissioners and audit committee size has a significant positive effect on the dividend payout ratio. This result is because female commissioners can take control of minority shareholders by making larger payments and audit committee members can monitor more effectively and control opportunistic behavior. However, board independence and board meeting significantly adversely affect the dividend payout ratio, this is because more members of board independence and more frequent meetings can use dividends as a substitute role in reducing agency problems so that dividend payment will be below. The observations on the TSE shows that the proportion of female independent commissioners and board meetings significantly positively affects the dividend payout ratio. However, board independence has a significant adverse effect on the dividend payout ratio. This result is because board independence tends to reduce agency costs, so using dividends as a substitute role to reduce dividend payments.